2013
DOI: 10.1007/s11248-013-9733-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced accumulation of atropine in Atropa belladonna transformed by Rac GTPase gene isolated from Scoparia dulcis

Abstract: Leaf tissues of Atropa belladonna were transformed by Sdrac2, a Rac GTPase gene, that is isolated from Scoparia dulcis, and the change in atropine concentration of the transformants was examined. Re-differentiated A. belladonna overexpressing Sdrac2 accumulated considerable concentration of atropine in the leaf tissues, whereas the leaves of plants transformed by an empty vector accumulated only a very low concentration of the compound. A. belladonna transformed by CASdrac2, a modified Sdrac2 of which translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…In fact, the effect of CrROP3 and CrROP5 overexpression was similar to the effect observed in silencing and overexpression of CrGGPPS2 , which provides GGPP precursor for CrPGGT-I (Kumar et al, 2020). In agreement with our results, overexpression of a type-I ROP from S. dulcis Sdrac2 enhanced the biosynthesis of tropane alkaloid atropine in A. bellodona (Asano et al, 2013), indicating a possibility of a similar scenario in other alkaloid producing plants. Although the transcript level of CrROP2 was significantly enhanced in both transient and stable overexpression backgrounds, it had no effect on either the transcript levels of TFs and genes related to MIA biosynthesis or the levels of secologanin and MIA (Figure 7).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In fact, the effect of CrROP3 and CrROP5 overexpression was similar to the effect observed in silencing and overexpression of CrGGPPS2 , which provides GGPP precursor for CrPGGT-I (Kumar et al, 2020). In agreement with our results, overexpression of a type-I ROP from S. dulcis Sdrac2 enhanced the biosynthesis of tropane alkaloid atropine in A. bellodona (Asano et al, 2013), indicating a possibility of a similar scenario in other alkaloid producing plants. Although the transcript level of CrROP2 was significantly enhanced in both transient and stable overexpression backgrounds, it had no effect on either the transcript levels of TFs and genes related to MIA biosynthesis or the levels of secologanin and MIA (Figure 7).…”
Section: Discussionsupporting
confidence: 92%
“…These studies highlight the significance of geranylgeranylation and indicate the involvement of geranylgeranylated proteins in the regulation of specialized metabolism in plants. Given this information, and considering that ROP proteins are known to undergo prenylation (Sorek et al, 2010; Sorek et al, 2011), and that overexpression of a ROP from S. dulcis ( Sdrac2 ) enhanced atropine content in A. belladonna (Asano et al, 2013), we hypothesized specific geranylgeranylated ROPs may play a role in the regulation of MIA biosynthesis in C. roseus . Hence, the current study aimed to conduct a detailed investigation on the role of ROPs in C. roseus MIA biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A ). Interestingly, CrROP3 and CrROP5 (group 1) clustered together with SdRac2 and AmRac2, GTPases that positively regulated the production of specific alkaloids and sesquiterpenes, respectively ( Asano et al 2013 ; Kurosaki and Taura 2015 ). Additionally, the sequence alignment showed that all CrROPs possess characteristic G-box motifs and a hyper-variable C-terminal region.…”
mentioning
confidence: 99%